Corallimorpharians (Anthozoa: Corallimorpharia) from the Argentinean Sea - Lauretta, Daniel; Martinez, Mariano I. (Zootaxa, 2019)
Corallimorpharians are a relative small group of anthozoan cnidarians, also known as jewel sea anemones. They resemble actiniarian sea anemones in lacking a skeleton and being solitary, but resemble scleractinian corals in external and internal morphology, and they are considered to be the sister group of the stony corals. Corynactis carnea (=Sphincteractis sanmatiensis) is a small, common and eye catching species that inhabits the shallow water of northern Patagonia and the Argentinean shelf up to 200 m depth. Corallimorphus rigidus is registered for the first time from the southwestern Atlantic Ocean. It is a rather big and rare species that inhabits only the deep sea. Only two specimens were found at 2934 m depth in Mar del Plata submarine canyon, in an area under the influence of the Malvinas current, which may explain its occurrence. These two species are the only two known jewel sea anemones in the Argentinean sea and are reported and described herein.